"A Person I Cared About Was Involved": Exploring Bystander Motivation to Help in Incidents of Potential Sexual Assault and Dating Violence. Issue 9 (May 2021) - Casper, Deborah M.; Witte, Tricia; Stanfield, Matthew H.
The purpose of the present study was to examine what motivates college students to put themselves in harm's way and help their peers in risky situations involving sexual assault and dating violence. College students reported on the frequency of witnessing a wide range of potentially dangerous incidents, whether or not they intervened, why they chose to intervene, what their relationship was to the victim, and reactions to their intervention. A sample of 182 (59.5% female) college students ( M age = 19.3 years) participated. We coded and analyzed narrative responses to the question regarding what influenced their decision to get involved. For female students, relationship to the victim, and, for males, the severity of the situation, were key motivational factors for bystander involvement. Some students reported positive feelings while others reported negative feelings directly related to their involvement. Tapping into the motivations underlying college students' helping behavior will be particularly informative for those designing and implementing bystander intervention programs on college campuses. A better understanding of bystander behavior will not only improve bystander intervention programs but it will also put students in the best position to make informed and responsible choices when faced with a difficult situation.